IMPLEMENTASI PROGRAM PEMBINAAN KARAKTER SANTRI MELALUI WORKSHOP DAN FIELD TRIP DI PESANTREN MODERN - Nurti Budiyanti; Asep Abdul Aziz; Andewi Suhartini; Nurwadjah Ahmad (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
The character of Islam needs to be nurtured early on in overcoming increasingly degrading moral degradation. One of the educational institutions that has a big role in fostering character is pesantren. Pesantren Kreatif IHAQI Boarding School Bandung is one of the pesantren educational institutions present in the era of industrial revolution 4.0. This pesantren has different characteristics in the process of building santri character. This research uses qualitative approach with case study method at IHAQI Boarding School Bandung Creative Boarding School. The results of the study illustrate that the coaching program presented at IHAQI Boarding School Creative Boarding School is a KBM program, islamic character habituation, self-development and life skills, weekly coaching, monthly coaching, creative coaching, and pesantrenan coaching. From a number of programs presented there are excellent programs that are always anticipated by all students as well as parents of students in the pesantren environment. There are two excellent programs in pesantren, namely workshop and filed trip. This excellent activity in pesantren is a unique and creative activity in developing life skills, both acting, working and speaking skills. This skill is aimed at the formation of santri character, so that students can behave in accordance with Islamic values based on the experience, knowledge and examples of educators.